Dynamics of Microplastic at Mangrove Forest in Ternate City: Distribution Spatial, Retention Sediment and Potential Bioremediation through Microbial of Plastic in Role Coastal Natural Barrier - Badrun Ahmad (Universitas Airlangga, 2026)
Introduction: The rate at which plastic is being produced 400 million tons annually today has created a widespread pollution of aquatic environments as plastics break down into ever smaller pieces (micro and nano) over time. Indonesian coastal ecosystems, especially mangroves, provide a natural buffer to microplastic (MP) pollution. They act as nurseries for a range of marine life, protect coastlines from erosion and store vast amounts of carbon, part of the “blue carbon” system that can sequester carbon for thousands of years. The spatial and vertical distribution of MPs, retention processes and microbe/particle interactions is explored in this study. Methods: MPs were isolated, morphologically sorted and identified for their polymer composition using stereomicroscopy and μFTIR, whereas root density, sediment organic carbon (SOC), methanogenic activity and microbial abundance were measured. Results and Discussion: MP loads significantly varied among zones (ANOVA, p 500 roots m⁻²) and sediments rich in organic matter. The higher MP loads led to more microbial activity, such as 16S rRNA gene copies (1.9–3.4 h x 10⁸ g⁻¹ DW) and methanogenic activities (0.12-0.27 mu mol CH₄ g⁻¹ DW d⁻¹; r = 0.67, p < 0.01). Native Pseudomonas sp. and Bacillus cereus had already biodegraded PE and PP at 7.4 ± 0.6% and 5.8 ± 0.4% up to 60 days, respectively. Conclusion: Ternate mangroves in shallow-waters are natural MP sink and dynamic microbial amphitheater, whereas chronic exposure to MPs would shift sediment biogeochemistry and threaten blue-carbon role.